Thinking through the politics of shame as a contemporary form of colonial discourse : analysing media representations of the Baby Tshepang rape case - Dutton, Jessica (African Studies, 2014)
In 2001, the rape of baby Tshepang triggered a media frenzy in the small community of Louisvale, located in the Northern Cape. An overarching theme of shame dominated how journalists represented the event. The label "A Town of Shame" stuck onto Louisvale through the mobilization of colonial and gender discourse. Quickly the town was known for its "barbarism" and "savage" existence; a town with no future and a disgrace to the country. Essentialist thinking about woman was used to condemn and blame the mother of baby Tshepang, concretizing the myth that rape is always the fault of women.